Evaluation potential of PGPR to protect tomato against Fusarium wilt and promote plant growth - Syed Nabi, Rizwana begum; Shahzad, Raheem; Tayade, Rupesh; Shahid, Muhammad; Hussain, Adil; Ali, Muhammad Waqas; Yun, Byung-Wook (PeerJ, 2021)
Soilborne fungal diseases are most common among vegetable crops and have major implications for crop yield and productivity. Eco-friendly sustainable agriculture practices that can overcome biotic and abiotic stresses are of prime importance. In this study, we evaluated the ability of plant growth-promoting rhizobacterium (PGPR) Bacillus aryabhattai strain SRB02 to control the effects of tomato wilt disease caused by Fusarium oxysporum f. sp. lycopersici (strain KACC40032) and promote plant growth. In vitro bioassays showed significant inhibition of fungal growth by SRB02. Inoculation of susceptible and tolerant tomato cultivars in the presence of SRB02 showed significant protection of the cultivar that was susceptible to infection and promotion of plant growth and biomass production in both of the cultivars. Further analysis of SRB02-treated plants revealed a significantly higher production of amino acids following infection by F. oxysporum. Analysis of plant defense hormones after inoculation by the pathogen revealed a significantly higher accumulation of salicylic acid (SA), with a concomitant reduction in jasmonic acid (JA). These results indicate that B. aryabhattai strain SRB02 reduces the effects of Fusarium wilt disease in tomato by modulating endogenous phytohormones and amino acid levels.
Keywords: PGPR; Bacillus aryabhattai; SRB02; Fusarium oxysporum; Tomato wilt; Tomato; Plant growth